Ruang Baru dalam Syariah: Respons Hukum Islam terhadap Gender Non-Biner - Salsabila Najma Chaniago (Arba: Jurnal Studi Keislaman, 2025)
The phenomenon of non-binary gender has become a hot topic in contemporary religious and social discourse, including in Sharia discourse. In classical fiqh, the concept of gender is generally limited to the dichotomy of male and female, with limited recognition of intersex individuals (khunṡā). However, the development of gender identity in the modern era challenges this binary paradigm, raising new questions about the position of non-binary gender in Islamic law. This study aims to examine the classical fiqh approach to non-binary gender, and to assess the extent to which contemporary thinking in sharia can respond to this reality fairly and inclusively. The method used is a qualitative literature study with a critical-analytical approach to classical and contemporary fiqh texts, as well as the interpretations of scholars on the concept of khunṡā and gender identity. The results of the study show that although classical fiqh does not explicitly recognize the term’ non-binary gender, several principles of maqāṣid al-Sharīʻah and the contemporary ijtihād approach allow for interpretive space to accommodate this identity. In conclusion, contemporary sharia discourse is required to develop a more responsive approach to social dynamics and diverse gender identities, without neglecting the main principles of sharia. This study makes an initial contribution to building a dialogue between the Islamic legal tradition and non-conventional gender issues.